Pengaruh Penggunaan Voltage Stabilizer Di Mesin KVY Pada Emisi Gas Buang, Konsumsi Bahan Bakar Dan Prestasi Mesin Yang Dihasilkan - W. Praja, Sumantri; Yudhanta, Ricko; Schouten, Femmy; Wijonarko, Bambang; Tri Indra, Guntur (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2025)
One solution to make the combustion that occurs in a motorbike closer to perfect is by utilizing the use of a Voltage Stabilizer. The performance of the Voltage Stabilizer is able to focus the electric current from the coil, so that the sparks emitted by the spark plugs are greater than before. Through the measurement results, in the condition of the Voltage Stabilizer installed, the lowest CO level was 0.72%vol, the lowest CO2 was 6.06%vol, the lowest HC was 1336 ppmvol occurred at an engine speed range of 5000 rpm. The lowest O2 level of 6.25%vol was obtained at an engine speed of 5000 rpm when the standard condition was without the Voltage Stabilizer installed. The highest O2 level obtained was 17.12%vol at an engine speed of 1000 rpm with the Voltage Stabilizer installed. The highest Torque (T) value was 8,722 Nm, and the highest Power (P) value was 8,414 PS at an engine speed range of 8000 rpm. Occurred when the Voltage Stabilizer was installed. With the installation of Voltage Stabilizer, it causes an increase in the Torque value of 11.93% and Power of 12.80% produced. The highest Fuel Consumption value of 0.642 Kg/h when the engine speed is in the range of 8000 rpm, occurs in conditions without the Voltage Stabilizer installed. The lowest Fuel Consumption value of 0.094 Kg/h when the engine speed is in the range of 1000 rpm, occurs in conditions with the Voltage Stabilizer installed. Furthermore, the installation of the Voltage Stabilizer causes a decrease in the Fuel Consumption value of 14.22%. This happens because the installation of the Voltage Stabilizer can stabilize the current and voltage obtained from the Battery/Accu to be distributed to the electrical components of the vehicle, so that there is efficiency in the vehicle's electrical supply, affecting emissions and fuel consumption produced.